Ultrathin, lightweight and flexible perovskite solar cells with an excellent power-per-weight performance. Issue 3 (19th December 2018) - Kang, Saewon; Jeong, Jaeki; Cho, Seungse; Yoon, Yung Jin; Park, Seungyoung; Lim, Seongdong; Kim, Jin Young; Ko, Hyunhyub
Abstract : Ultralight and flexible perovskite solar cells with the orthogonal AgNW electrodes exhibit an excellent power-per-weight of 29.4 W g −1 . Abstract : Lightweight and flexible photovoltaic devices have attracted great interest for specific potential applications, such as miniaturized drones, blimps, and aerospace electronics. This study aims to demonstrate ultralight and flexible perovskite solar cells (PSCs) with orthogonal silver nanowire (AgNW) transparent electrodes fabricated on 1.3 μm-thick polyethylene naphthalate foils. The smooth surface morphologies of the orthogonal AgNW transparent electrodes help prevent nonconducting silver halide formation generated by chemical reaction between the AgNWs and iodine in the active layer. The resultant PSCs with orthogonal AgNW transparent electrodes exhibit substantially improved device performance, achieving a power conversion efficiency (PCE) of 15.18%, over PSCs with random AgNW network electrodes (10.43% PCE). Moreover, ultralight and flexible PSCs with the orthogonal AgNW electrodes exhibit an excellent power-per-weight of 29.4 W g −1, which is the highest value reported for a lightweight solar cell device. These lightweight energy harvesting platforms can be further expanded for various wearable optoelectronic devices.